A Rare Manifestation of Tuberculosis Presenting in the United States. (22nd December 2016) - Bhatty, Osman; Waters, David; Wilka, Nicholas; Samuel, Shradha; Horne, John; Vivekanandan, Renuga
Abstract : A 64-year-old Bangladeshi female presented to her primary care physician with a tender right breast lump that had been present for 4-5 days along with subjective fevers and malaise. Initial biopsy revealed granulomas, but Ziehl-Neelsen and Gram stain were negative for TB so antibiotics were prescribed for abscess until culture came positive for tuberculosis. She was started on triple therapy for extrapulmonary tuberculosis, an exceedingly rare presentation that requires high clinical suspicion in the Western world.